Exposure and Markups - Allayannis, George; Ihrig, Jane (Review of Financial Studies, 2001)
This article examines how to properly specify and test for factors that affect exchange-rate exposure. Starting from theoretical underpinnings and a sample of U.S. manufacturing industries between 1979 and 1995, we find that 4 of 18 industry groups are significantly exposed to exchange-rate movements through the effect of industry competitive structure, export share, and imported input share. On average, a 1% appreciation of the dollar decreases the return of the average industry by 0.13%. Consistent with our model’s predictions, as an industry’s markups fall (rise), its exchange-rate exposure increases (decreases).